The reflective equilibrium in Rawls’ theory of justice: The perspective of holistic pragmatism - Mihai BURLACU (Meta: Research in Hermeneutics, Phenomenology, and Practical Philosophy, 2015)
Interpreting John Rawls’ ‘reflective equilibrium’ method from the perspective of Morton White’s holistic pragmatism entails both an epistemological and a methodological dimension. In this article, I reconsider White’s perspective regarding Rawls’ ‘reflective equilibrium’. This requires a critical examination of the method’s origins and development, with an emphasis on Nelson Goodman’s process of justification and the Duhem-Quine thesis. In order to examine the origins and development of the ‘reflective equilibrium’ method, I also draw upon the writings of Pierre Duhem, Willard Van Orman Quine, Nelson Goodman, Stephen P. Stich and Donald Gillies, among others. Subsequently, I interpret the criticisms that have been formulated against the process of justification elaborated by Goodman and adapted by Rawls. Afterwards, I explain the conceptual links between the ‘Duhem-Quine thesis’ and the ‘reflective equilibrium’ method. In the last chapter, I analyse White’s assertion that Rawls’ theory of justice is a variant of holistic pragmatism. I emphasize how White’s holistic theses coincide to a significant extent with the ideas devised by Rawls regarding the method of ‘reflective equilibrium’ in social justice, and in a more general sense, in ethics. Also, I expound why White’s doctrine is epistemologically holistic and methodologically monistic.
Meta: Research in Hermeneutics, Phenomenology, and Practical Philosophy 2015-12-10 | Journal article EID: 2-s2.0-84954438930 Part of ISSN: 20673655 WOSUID: WOS:000215854900008 URL: http://www.metajournal.org/article_details.php?id=247
Keywords: reflective equilibrium; holistic pragmatism; considered judgment; principles of justice; conjunction of statements; Duhem-Quine thesis; Duhemian conjunction